Reliability-Based Reassessment of Starter-Generator Preventive Maintenance Intervals on ATR 72-212A Aircraft Using Operational Removal Data - Yoga Yulasmana; Bobi Gumelar Raspati (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2026)
This paper re-assesses the preventive maintenance interval of starter-generator part number 8260-124 installed on ATR 72-212A aircraft using operational removal data from Airline X between 2019 and 2024. A quantitative case-study approach was applied to 65 removal records, comprising 39 scheduled and 26 unscheduled removals. The analysis included failure-mode classification, Pareto analysis, statistical distribution fitting, Mean Time to Failure estimation, survival analysis, Component Removal Rate, and Mean Time Between Unscheduled Removal. Brush wear was identified as the dominant failure mode, accounting for 53.8% of unscheduled removals. The lognormal distribution provided the best fit to the Time Since Installation data, with an adjusted Anderson–Darling statistic of 0.746 and a correlation coefficient of 0.989. The estimated MTTF was 907.022 flight hours, substantially below the existing 1,200-flight-hour maintenance interval, while the survival probability declined to 51.6% at 900 flight hours and 13.1% at 1,000 flight hours. These findings indicate that the current interval provides insufficient preventive margin. Therefore, an 800-flight-hour interval is recommended to reduce brush-related deterioration, unscheduled removals, and associated operational disruptions.